2011
DOI: 10.1111/j.1468-3083.2011.04223.x
|View full text |Cite
|
Sign up to set email alerts
|

Repeated exposure of human fibroblasts to UVR induces secretion of stem cell factor and senescence

Abstract: These results suggest that fibroblast senescence and increased SCF secretion after repeated UV irradiation may be related to the pathogenesis of recurring hyperpigmentation disorders induced by chronic sun exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 20 publications
1
42
0
Order By: Relevance
“…This result suggests that SCF in the dermis may play a role in the development of melasma. It is possible that the inflammation in the dermis from the accumulated Ultraviolet Rays (UVR) may be associated with activation of fibroblasts and melanocytes leading to their increased proliferation and melanogenesis respectively [24]. These findings also were similar to another study, they were surprised by the unexpected evidence of damage to basal membrane, which could facilitate the fall or the migration of active melanocytes and melanin into the dermis allowing the constant hyperpigmentation in melasma [25].…”
Section: Histopathological Results (Hande)supporting
confidence: 70%
See 1 more Smart Citation
“…This result suggests that SCF in the dermis may play a role in the development of melasma. It is possible that the inflammation in the dermis from the accumulated Ultraviolet Rays (UVR) may be associated with activation of fibroblasts and melanocytes leading to their increased proliferation and melanogenesis respectively [24]. These findings also were similar to another study, they were surprised by the unexpected evidence of damage to basal membrane, which could facilitate the fall or the migration of active melanocytes and melanin into the dermis allowing the constant hyperpigmentation in melasma [25].…”
Section: Histopathological Results (Hande)supporting
confidence: 70%
“…It is also known as ligand mast cell growth factor. In response to various stimuli, keratinocytes secrete cytokines as SCF and c-kit so the levels of SCF secreted and c-kit increases in skin hyperpigmentation as melasma [24]. Patients who received topical or systemic treatment in the past 6 weeks, prior to the incorporation in this study and patients who have other dermatological or systemic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the hereditary disorders Werner syndrome, xeroderma pigmentosum, and Hutchinson–Gilford progeria syndrome, which are due to defects in DNA damage repair or nuclear organization, are associated with increased cellular senescence and accelerated age related phenotypes in the skin (Davis et al , 2007; Harada et al , 1999; Liu et al , 2006). Extrinsic factors, such as X-rays, ultraviolet (UV) light, and cigarette smoke, also can induce cellular senescence as well as age related phenotypes in the skin (Shin et al , 2012; Velarde et al , 2012; Yang et al , 2013). …”
Section: Cellular Senescence and Skin Agingmentioning
confidence: 99%
“…Consistent with these early findings, later work demonstrated that the critical tumor suppressor and senescence mediator, p16, likewise accumulated in aged epidermis and dermis in vivo (Ressler et al, 2006). Further connecting senescence and skin aging, UVR is known to induce the DDR, SASP-like inflammation, and senescence in vitro (Shin et al, 2012), and is directly associated with human photoaging and p16 positivity in the skin in vivo (Nakanishi et al, 2009). Prominent SASP proteases such as MMP1 have been shown to degrade collagen in the skin and lead to UV-induced photoaging (Quan et al, 2013).…”
Section: Introductionmentioning
confidence: 99%